Effect of Fly Ash Percentage on Compaction Parameters of a Fill Material - Situngkir , Hegi Priel; Nugraha, Andrias Suhendra; Riyadi, Slamet (Jurnal Teknik Sipil, 2025)
Mining road construction is heavy equipment infrastructure for transportation that carries mining products to facilitate activities. Mining road construction requires high costs, with this research it is hoped that it can utilize by utilizing leftover materials or non-B3 waste around the mining area, it can save costs for mining road construction. This research aims to understand and assess the effect of fly ash presentation originating from coal burning residue from the mining area in Tanjung Selor, North Kalimantan, on the compaction parameters of a fill material that will be used as mining road material. These compaction parameters include maximum dry density, gdry max and optimum moisture content, wopt. The composition of the mixture between fly ash (FA) and fill material (FM-I) includes: FA(50%)+FM-I(50%) and FA(70%)+FM-I(30%).The research results show that increasing the fly ash presentation from 50% to 70% in a mixture of fly ash and fill material will increase the optimum moisture content from 12.9% to 21.9% and will reduce the maximum dry density from 1.44 t/m3 to 1.20 t/m3. The presentation of fly ash affects the compaction parameters of the fill material.